Magnetic Resonance Imaging–Based Morphometric Analysis of the Tentorial Notch in a North Indian Population: A Descriptive Anatomical Study - Panda, Ashwin K.; Sadhashivam, Saravanan; Arora, Rajnish K.; Mittal, Radhey Shyam; Saxena, Sudhir; Nandolia, Khanak (Indian Journal of Neurosurgery, 2025)
Anatomical variabilities in the morphometric characteristics of the tentorial notch have been demonstrated through cadaveric studies on humans. Nevertheless, it is important to note that the measurements may be subject to variability due to postmortem effects. The aim of the study was to assess the morphometry of the tentorial notch in living individuals using magnetic resonance imaging (MRI).A retrospective cross-sectional study was conducted and 1,043 cases were analyzed for the institutional archive from January 2021 till December 2022. Variables measured were maximum notch width (MNW), anterior notch length, notch length (NL), interpedunculoclival distance, and apicotectal distance using RadiAnt DiCom viewer. A quartile distribution technique was applied to all measurements and patients were classified into different types of tentorial notch.We studied 1,043 patients between the ages of 2 months and 84 years with normal MRI scans. Quartile analysis was applied to all measurements. Based on the quartile group, MNWs were classified into wide, narrow, and midrange, and NLs were classified into long, short, and midrange. According to criteria established by Adler and Milhorat, classification of tentorial notch was done and we found the following: short and wide (4.2%), short and medium (12%), short and narrow (9.1%), medium and wide (12.4%), classical (25.3%), medium and narrow (12.4%), long and wide (8%), long and medium (12.6%), and long and narrow (4%).The dimension of tentorial notch significantly varies among different age groups. NL and MNW are significantly larger in those above 60 years of age. Typical type of notch was the most common variety in our sample and short wide and long narrow were least common types.
Keywords: herniation; magnetic resonance imaging; morphometry; neuroimaging; tentorial notch